Searching for the next new energy in energy transition: Comparing the impacts of economic incentives on local acceptance of fossil fuels, renewable, and nuclear energies - Kim, Seoyong; Lee, Jae Eun; Kim, Donggeun (Sustainability (Switzerland), 2019)
This study compares the impacts of economic incentives on attitudes related to the acceptance of fossil fuels, renewable, and nuclear energies. Linear and nonlinear regression models are applied for the robust estimation results. Empirical findings based upon these regression models are summarized as follows: First, when people belong to the upper social class, reside in metropolitan area, and have more trust in the government's energy policy, they tend to accept the construction of specific energy-related facilities in a neighborhood and raise the probability of attitude change and stability. Second, those who have more perceived risk and negative image are less likely to accept any types of energies and tend to lower the probability of attitude change toward positive direction or stability. Third, those who have more knowledge are less likely to accept some energy sources such as fossil fuels and there exists a trade-off relationship between knowledge and trust. Finally, the structural changes between acceptance of all energy sources with and without economic incentives imply that economic incentives play a significant role in determining acceptance of energies.
Keywords: Acceptance of fossil fuel energy; Acceptance of nuclear energy; Acceptance of renewable energy; Attitude change; Economic incentive